SIMPLE MICRONEEDLING VERSUS MICRONEEDLING WITH TOPICAL INSULIN IN THE TREATMENT OF POST ACNE ATROPHIC SCARS; A SPLIT FACE COMPARATIVE STUDY - Mira Ali; Najia Ahmed; Seemab Khan; Afshan kiran (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acne vulgaris is a common skin condition, involving upto 90% of the teenage population, being more common in women than in men. Post acne scars are the sequelae, leading to low esteem and self confidence in the affected individuals. Methods: Thirty patients participated in the study. On each patient, over the left side of the face, microneedling was done using topical insulin as a medium, while on the right side of the face, simple microneedling was done. Four such sessions, a month apart, were done in all the patients. They were called for follow up and the response was based on the "Acne scar assessment scale", in which Grade-0 referred to no improvement, Grade-1 referred to an improvement of less than 25%, Grade-2 was an improvement between 25–50%, Grade-3 meant an improvement between 50–75%, and, Grade-4 referred to an improvement of greater than 75%. Results: After completion of the sessions, over the left side of the face, where microneedling was done with insulin 11 (36.7%) patients showed Grade-2 improvement, while 19 (63.3%) patients showed Grade-3 improvement. On the right side of the face where simple microneedling was done, 10 (33.3%) patients showed an improvement of Grade-0, and 20 (66.6%) patients showed an improvement of Grade-1. Conclusion: After this study, we conclude that microneedling combined with topical insulin, shows better results in patients with scarring. It can be a breakthrough in the treatment of post acne scars, due to easier availability and lesser cost of insulin.